The Value of Cancer Immunotherapy Summit at the 2016 Society for Immunotherapy of Cancer 31st Anniversary Annual Meeting. Issue 1 (18th April 2017) - Kaufman, Howard L.; Atkins, Michael B.; Dicker, Adam P.; Jim, Heather S.; Garrison, Louis P.; Herbst, Roy S.; McGivney, William T.; Silverstein, Steven; Wigginton, Jon M.; Yu, Peter P.
Abstract : As healthcare costs continue to rise, there has been great interest in understanding and defining the value of current therapeutic strategies for the treatment of cancer. Cancer immunotherapy has emerged as a clinically beneficial alternative to conventional therapies for a variety of malignancies. Characterized by broad clinical activity, durable response rates, distinct side effects, and unique response kinetics, immune-based agents are vastly different compared with traditional cytotoxic or targeted therapies. To date, however, value assessments in oncology have not focused on the unique aspects of cancer immunotherapy, which has resulted in a lack of understanding of the true value of these therapies. Therefore, the Society for Immunotherapy of Cancer (SITC) convened key stakeholders to address the critical issues that define the value of cancer immunotherapy in National Harbor, Maryland on November 13, 2016. Organized in collaboration with the American Society for Clinical Oncology (ASCO) and with over 1500 registrants, this Value of Cancer Immunotherapy Summit united research scientists, academic physicians, industry professionals, health economists, third-party payers, and patients to discuss critical issues surrounding the value framework for cancer immunotherapy. This half-day summit addressed the current landscape of cancer therapy value models, economic outcomes, the current status of predictive biomarkers, as well as presentations from third-party payers, industry representatives, patient outcome experts, and patient advocacy groups to gain their perspectives on the value of cancer immunotherapy. Here, we summarize the presentations and the dominant themes from this symposium, with the intention of providing insight on future directions and to develop recommendations to better define the value of cancer immunotherapy for patients with cancer.